Cutaneous manifestations of SARS‐CoV‐2 infection: a clinical update. (20th July 2020) - Gisondi, P.; PIaserico, S.; Bordin, C.; Alaibac, M.; Girolomoni, G.; Naldi, L.
Abstract: On 11 March 2020, the World Health Organization (WHO) has declared the novel coronavirus disease (COVID‐19) a global pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2 virus). A consistent number of case reports and clinical series have been already published describing a complex spectrum of skin manifestations associated with the SARS‐CoV‐2 infection. We carried out a review of the English‐language literature up to 20 May 2020, reporting original cases or case series of the cutaneous manifestations of SARS‐CoV‐2 virus infection. The following databases were consulted: PubMed, Embase, Google Scholar and ResearchGate. The search of papers was conducted by using the key term 'COVID‐19' or 'SARS‐CoV‐2' or 'coronavirus' combined with each of the following: 'skin', 'cutaneous', 'dermatologic' or 'dermatology', 'manifestation', 'lesions', or 'rash'. The patterns of dermatological manifestations associated with SARS‐CoV‐2 infection could be classified into four categories: exanthema (varicella‐like, papulo‐vesicular and morbilliform rash), vascular (chilblain‐like, purpuric/petechial and livedoid lesions), urticarial and acro‐papular eruption. Lastly, other skin manifestations to be considered are the cutaneous adverse reactions to the drugs prescribed for the treatment of COVID‐19. Whether SARS‐CoV‐2 infection can directly cause a worsening of chronic inflammatory diseases such as psoriasis or atopic dermatitis remains to be determined. Dermatology's outlook in the COVID‐19 pandemic is multidimensional.